2013
DOI: 10.1111/ajt.12332
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Test Technique on Sensitization Status of Patients on the Kidney Transplant Waiting List

Abstract: The exquisitely sensitive single antigen bead (SAB) technique was shown to detect human leukocyte antigen (HLA) antibodies in sera of healthy male blood donors. Such false reactions can have an impact on critical decisions, especially with respect to the determination of unacceptable HLA-antigen mismatches in patients awaiting a kidney transplant. We tested pretransplant sera of 534 patients on the kidney waiting list using complement-dependent cytotoxicity (CDC), enzyme-linked immunosorbent assay (ELISA) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
66
0
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(81 citation statements)
references
References 21 publications
(26 reference statements)
4
66
0
3
Order By: Relevance
“…Interpreting HLA or other antibodies as pathogenic requires expert opinion and is moving toward probabilistic assessment (28)(29)(30)(31), but this will often preclude the simple designation as ''positive versus negative'' specified in the Banff guidelines. For example, preexisting class I DSA has ABMR, antibody-mediated rejection; DSA, donor-specific antibody; NDSA, non-donor-specific HLA antibody.…”
Section: Discussionmentioning
confidence: 99%
“…Interpreting HLA or other antibodies as pathogenic requires expert opinion and is moving toward probabilistic assessment (28)(29)(30)(31), but this will often preclude the simple designation as ''positive versus negative'' specified in the Banff guidelines. For example, preexisting class I DSA has ABMR, antibody-mediated rejection; DSA, donor-specific antibody; NDSA, non-donor-specific HLA antibody.…”
Section: Discussionmentioning
confidence: 99%
“…The recent widespread application of SPA-based tests in clinical practice has confirmed the higher sensitivity of these diagnostic methods. Conflictingly, however, a growing number of studies in kidney transplantation patients have also shown that only a portion of Luminex-detectable HLA antibodies appear to cause antibody-mediated rejection [25][26][27]. This differentiation between clinically relevant and irrelevant DSAs is a major challenge, both before and after kidney [24,27,28].…”
Section: Detection Of Hla Antibodiesmentioning
confidence: 99%
“…Conflictingly, however, a growing number of studies in kidney transplantation patients have also shown that only a portion of Luminex-detectable HLA antibodies appear to cause antibody-mediated rejection [25][26][27]. This differentiation between clinically relevant and irrelevant DSAs is a major challenge, both before and after kidney [24,27,28]. For example, the pathogenetic roles of different Ig subclasses or those of complement-and non-complement-fixing DSAs in antibody-mediated rejection are controversially discussed [29].…”
Section: Detection Of Hla Antibodiesmentioning
confidence: 99%
“…The significance of the DQ antibodies is increasingly recognized following the introduction of the SAB assay which considered today to be the most sensitive and specific method for alloimmunization assessment [13][14][15]. However, it is becoming clear that the detection of the HLA antibodies by SAB is not absolutely perfect due to the variation in densities and orientations of the antigen coated beads [16][17][18]. HLA-DQ antigen consists of two (αβ) polymorphic chains [19].…”
Section: Discussionmentioning
confidence: 99%